2021
DOI: 10.21203/rs.3.rs-189997/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Analysis of Metagenomic Next-generation Sequencing Confirmed Chlamydia psittaci Pneumonia: A Case Series and Literature Review

Abstract: Introduction: Chlamydia psittaci infection is a zoonotic infectious disease, which mainly inhaled through the lungs when exposed to the secretions of poultry that carry pathogenic bacteria. The traditional respiratory specimens or serological antibody testing is slow and the false-negative rate is high. Metagenomic next-generation sequencing gives a promising rapid diagnosis tool. Methods: We retrospective summarized the clinical characteristics of five C. psittaci pneumonia patients diagnosed by mNGS, conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Previous studies on psittacosis pneumonia have reported inconsistent results owing to the small number of patients and lack of separate analysis of drug treatment for mild and severe patients. [5,15,29,31] In this study, most patients received quinolones before diagnosis, of which some non-severe patients showed a good response to treatment, whereas severe patients showed a poor response. Therefore, using quinolones alone is not recommended in severe patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies on psittacosis pneumonia have reported inconsistent results owing to the small number of patients and lack of separate analysis of drug treatment for mild and severe patients. [5,15,29,31] In this study, most patients received quinolones before diagnosis, of which some non-severe patients showed a good response to treatment, whereas severe patients showed a poor response. Therefore, using quinolones alone is not recommended in severe patients.…”
Section: Discussionmentioning
confidence: 91%
“…C psittaci is transmitted after the inhalation of aerosolized bacterial cells, [10,11] which can rapidly cause severe respiratory failure and even death. [5,12] High-risk factors for infection include old age, smoking, male sex, glucocorticoid use, and long-term residence in nursing homes. The prognosis of patients is directly associated with immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psittacosis is a zoonotic disease caused by Chlamydia psittaci [3,4]. Patients infected with Chlamydia psittaci have infiltration and exudation of inflammatory cells in the alveoli, resulting in significant thickening of the alveolar wall and interstitial lung mass, edema, and necrosis [5].…”
Section: Primary Sjögren's Syndrome Combined With Chlamydia Psittaci ...mentioning
confidence: 99%